Assessing the likelihood of the soil surface to condense vapour: The Negev experience. Issue 3 (24th February 2020) - Kidron, Giora J.; Kronenfeld, Rafael
Abstract: The likelihood of dew to provide water to cyanobacteria (CB) and crustose lichens (CL) on soil is a matter of great controversy. Although vapour condensation takes place on cobbles of the Negev Highlands, facilitating lush cover of CL, controversy exists regarding the possible contribution of dew to CB and CL inhabiting the loessial soil of the Negev Highlands. To evaluate this matter, temperature, and measurements of the nonrainfall water (NRW) were conducted during the dewy season (August–November 2019). They included periodical NRW measurements using cloths attached to the (a) soil surface, (b) on top of 10 × 10 × 5‐ to 6‐cm cobbles, and (c) on 10 × 10 × 0.2‐cm glass plates (the cloth‐plate method, CPM). Additionally, temperature measurements took place at the soil and the cobble surfaces and in the air at 10‐cm height above ground. Air temperature and the relative humidity measured by an adjacent meteorological station facilitated the calculation of the dew‐point temperature (Td). Taking the CPM as reference, 24 mornings with NRW ≥0.03 mm (the threshold of lichen metabolism) were recorded. Vapour condensation, that is, NRW ≥0.1 mm were recorded during 16 mornings on the cobbles (with a maximum of 0.21 mm) but never on the soil, where maximum NRW reached only 0.023 mm. Surface temperature never reached Td. We therefore conclude that unlike lithic lichens that inhabit bedrocks and cobbles in the Negev Highlands, dew cannot be regarded as a meaningful direct source of water for CB or CL biocrusts on soil.